Physiotherapy Management for Osteoarthritis Knee for Grade II: A Case Report - Aunnillah, Raden Roro Aneta Jihan; Fatmarizka, Tiara; Efendi, Elif Nur (Universitas Muhammadiyah Surakarta, 2022)
Introduction: Osteoarthritis Knee (OA) is the most common condition during that elderly the quality of life, and a previous study has found that the most widely recognized type of osteoarthritis influencing up to 25% of people over the age of 50 years with many progressing to knee replacement surgery. Current clinical practice guidelines recommend knee replacement surgery only after first-line and second-line management options have been exhausted. Such non-surgical management options include patient education, exercise therapy, weight management and advice about pharmacological management of symptoms. Osteoarthritis Knee is the most well-known kind of joint inflammation and portrays the degeneration of the joints. Whilst most experience moderately mellow manifestations, for one in ten individuals, their knee agony and joint solidness are incapacitating. OA Knee were two of the top 20 search terms in an analysis of the searches conducted of the Physiotherapy Evidence Database (PEDro).Case Presentation: A 59 years male. He as the a ex-work officer residing in Magetan, EastJava. Examinations that have been carried out on the patient found muscle stiffness and tenderness and pain in motion and positive findings were also found during a specific examination using the anterior drawer test and the Lachman test.Management and Outcome: Mobilitation knee and technology modalities (Infrared and Ultrasound) could improve functional status, decreased the level and intensity of pain, and raise the quality of life among elderly man were the benefit of physiotherapy management for solving the knee problems.Discussion: Several studies have revealed that the use of infrared, TENS, ultrasound modalities, Muligan’s mobilization by adding muscle strengthening exercises quadriceps have a positive effect in reducing pain and stretching in muscles hamstring in cases of OA Knee. The author tries to prove it by applying several modalities that have been studied previously.Conclusion: Physiotherapy management in the Praktik Fisioterapi Magetan setting use the three to ten weeks of exercise program. The specific technique of exercise and mobilitation knee were used to treat the knee problems among OA elderly man.